Subcritical water technology for wheat straw hydrolysis to produce value added products - Abdelmoez, Wael; Nage, Soah M.; Bastawess, Ali; Ihab, Ahmed; Yoshida, Hiroke (Elsevier, 2014)
The cellulosic nature of agriculture wastes makes them suitable raw materials for conversion processing to produce end products with high value added. The present works described the using of subcritical water technology for the utilization of wheat straw through hydrolysis to produce reducing sugar. The experiments were carried out under different conditions and the optimum hydrolysis parameters were investigated. The results revealed that the optimum conditions for hydrolysis were 190 °C temperature, 30 min hydrolysis time, water to straw ratio of 6/1 and feedstock particle size of 180–355 μm. The maximum obtained yield the reducing sugars (RS) under the optimum hydrolysis condition amounted to 51.5% (as weight percent) of the raw wheat straw. HPLC analysis for the produced RS showed the presence of 3.2% of total RS as glucose and 7.6% as xylose, the balance being other reducing sugars, e.g. arabinose, galactose and probably other oligomers. Finally, the ethanol production from the produced glucose was tested through fermentation process. Based on the obtained results, it was possible to propose a design for a process combining both sugars and bioethanol production.